Modifications of the leaf surface structures of Quercus ilex L. in open, naturally CO2-enriched environments - Paoletti, E.; Nourrisson, G.; Garrec, J. P.; Raschi, A. (Plant, Cell & Environment, 1998)
Two Italian CO2 springs allowed us to study the long-term effect of a 350–2600 μmol mol–1 increase in CO2 concentrations on the surface structures of leaves of Quercus ilex L. Carbon dioxide increased the quantity of cuticular waxes, above an apparent threshold of 750 μmol mol–1 CO2. Leaf wettability was not modified by CO2 concentrations. Reduction in stomatal frequency was observable up to 750 μmol mol–1 CO2, the slope being almost the same as that estimated for the increase in CO2 concentration from pre-industrial times to the present. At higher concentrations, CO2 seemed to exert no more impact on stomatal frequency.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Elevated CO2; leaf wettability; natural CO2 spring; Quercus ilex; stomatal frequency; wax amount